2017
DOI: 10.1021/acs.jpcc.7b02253
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical Properties of GaN Photoanodes with Cobalt Phosphate Catalyst for Solar Water Splitting in Neutral Electrolyte

Abstract: Cyclic voltammetry measurements are carried out in neutral phosphate-buffered electrolyte using n-type Gapolar GaN thin-film photoelectrodes with and without cobalt phosphate (Co-Pi) modification. Without Co-Pi, the variation of the photocurrent with the bias potential exhibits a two-step behavior and under chopped illumination spikes occur at low bias potential. Thus in this regime surface recombination is dominant. Co-Pi modification suppresses surface recombination and significantly increases the photocurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Usually, spikes in the transient photocurrent measurements indicate surface recombination, due to the presence of the surface states or slow water oxidation kinetics. SnO 2 /WO 3 /BiVO 4 photoanode shows negligible spikes and a steady photocurrent, which demonstrates that the holes accumulated at the surface readily react with the water and hence improve photocurrent density without producing transient spikes [31].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Usually, spikes in the transient photocurrent measurements indicate surface recombination, due to the presence of the surface states or slow water oxidation kinetics. SnO 2 /WO 3 /BiVO 4 photoanode shows negligible spikes and a steady photocurrent, which demonstrates that the holes accumulated at the surface readily react with the water and hence improve photocurrent density without producing transient spikes [31].…”
Section: Resultsmentioning
confidence: 95%
“…It indicates that the SnO 2 50 nm/WO 3 50 nm/BiVO 4 has high charge separation efficiency and high water oxidation kinetics. photocurrent, which demonstrates that the holes accumulated at the surface readily react with the water and hence improve photocurrent density without producing transient spikes [31]. Further, charge transfer properties have been investigated by Nyquist plots.…”
Section: Resultsmentioning
confidence: 97%
“…It is reported that Co-Pi can change the reaction pathway to reduce overpotential and promote surface charge transfer kinetics. [96,109] For example, Carroll and Gamelin [96] reported that water-oxidation kinetics of α-Fe 2 O 3 actually gets slow after the deposition of Co-Pi, but electron-hole recombination slows even more, resulting in a net enhancement of water-oxidation quantum efficiency, which is opposite to previous expectations. Meanwhile, as the change in valence state of Co ion is invertible, the accumulation of photoinduced holes at the interface of electrode and electrolyte can be relieved timely and effectively and then an improved PEC performance can be achieved.…”
Section: Metal Phosphatesmentioning
confidence: 90%
“…Since then, this catalyst has gained numerous interests and become one of the research hotspots. [96,102,[108][109][110][111][112] Some further clarified the mechanism of the Co-Pi applied on semiconductors. [107] Co 2+/3+ of Co-Pi can be oxidized to a higher valence state of Co 4+ under the effect of current or holes, and then Co 4+ can be reverted back to Co 2+/3+ rapidly after it oxidized water molecules or sacrificial agents, [50] which is recognized as an entire catalytic reaction cycle.…”
Section: Metal Phosphatesmentioning
confidence: 99%
“…Moreover, Co-Pi-modified GaN photoaonde has shown some improvement in the onset potential and the photocurrent but poor resistance against photocorrosion 16 .…”
Section: Introductionmentioning
confidence: 99%